Government crisis communication tools in the light of the extreme drought of 2022 - Ágnes Kovács; Edina Kriskó; Tamás Pálvölgyi; László Balatonyi (Belügyi Szemle)
Aim: The purpose of this study is to investigate the communication of the drought (water crisis) of 2022. As water is a vital element, the alpha and omega of survival, the authors should expect the emergence of existential anxieties during related crises that may result in messages being ignored. This makes the communication of the responsible public authority even more difficult. The authors’ aim to make forward-looking recommendations for water professionals in the face of future water crises.